Propaedeutics of Mathematical Language of Schemes and ￼Structures in School Teaching of the Natural Sciences Profile - V. P. Kotchnev (Образование и наука)
The paper looks at the teaching process at schools of the natural sciences profile. The subject of the research is devoted to the correlations between the students’ progress and the degree of their involvement in creative activities of problem solving in the natural sciences context. The research is aimed to demonstrate the reinforce- ment of students’ creative learning by teaching mathematical schemes and structures. The comparative characteristics of the task, problem and model approaches to mathematical problem solving are given; the experimental data on the efficiency of mathematical training based on the above approaches being discussed, as well as the specifics of modeling the tasks for problem solving. The author examines the ways for stimulating the students’ creative activity and motivating the knowledge acquisition, and search for the new mathematical conformities related to the natural science content. The significance of the Olympiad and other non-standard tasks, broadening the students’ horizons and stimulating creative thinking and abilities, is emphasized.The proposed method confirms the appropriateness of introducing the Olympiad and non-standard problem solving into the preparatory training curricula for the Unified State Examinations.